Refractive outcomes after trabecular microbypass stent with cataract extraction in open-angle glaucoma - Scott RA (Dove Medical Press, 2019)
Rachel A Scott,1 Tanner J Ferguson,2 John D Stephens,3 John P Berdahl31Baylor College of Medicine, Houston, TX, USA; 2Sanford School of Medicine, University of South Dakota, Vermillion, SD, USA; 3Vance Thompson Vision, Sioux Falls, SD, USAPurpose: To evaluate the impact of trabecular microbypass stents combined with cataract surgery on refractive outcomes in patients with open-angle glaucoma (OAG).Setting: Private practice, Sioux Falls, South Dakota, USA.Design: Retrospective, comparative case series.Methods: Eyes with OAG had implantation of trabecular microbypass stents with concomitant cataract surgery. The unmatched control group comprised eyes that underwent only cataract extraction. Data were collected preoperatively and postoperatively for 6 months. Data included spherical equivalent (SE), astigmatic error, intraocular pressure (IOP), and number of glaucoma medications.Results: The series included 76 consecutive OAG eyes with combined cataract plus trabecular microbypass stent and 50 consecutive non-OAG eyes with cataract surgery only. SE outcomes were equivalent between the groups (P<0.001). For the combined and cataract-only groups respectively, 46% vs 52% had SEs within 0.25 D of the target, 80% vs 80% within 0.50 D, and 95% vs 94% within 1.00 D. Astigmatism outcomes did not significantly differ between the groups (P>0.05). As for magnitude of astigmatism in the combined and cataract only groups respectively, 51% vs 32% were within 0.5 D, 75% vs 66% within 1.0 D, 87% vs 82% within 1.5 D, and 89% vs 94% within 2.0 D. In the OAG combined–surgery group, mean intraocular pressure reduction was 3.4 mmHg (P<0.0001) at 1 month postoperatively, 4.0 mmHg (P<0.0001) at 3 months, and 3.4 mmHg (P<0.01) at 6 months. Mean decrease in number of glaucoma medications was 0.4 (P<0.05) at 1 month, 0.7 (p<0.0001) at 3 months, and 0.9 (P<0.001) at 6 months.Conclusion: The results of this study suggest the trabecular microbypass stent is a refractively neutral device.Keywords: MIGS, glaucoma, refractive, outcomes, cataract surgery